Analisis Termoelektrik Generator (TEG ) Sebagai Pembangkit Listrik Bersekala Kecil Terhadap Perbedaan Temperatur - M, Muharnif; Umuani, Khairul; Nasution, Firman AlwiArif (Rekayasa Material, Manufaktur dan Energi, 2022)
Electrical energy has now become a major need for the community, so it is necessary to develop alternative sources of electrical energy that are environmentally, not only on a large scale but also on a small scale. Thermoelectric Generator is a power plant that works based on the Seebeck effect, where the temperature difference between the hot and cold surfaces of these 2 electronic components is converted into electrical energy on a small scale. This study aims to analyze the effect of temperature differences that occur on the electrical energy produced in a thermoelectric. This research was studied by comparing the difference in heat generated from 1, 2 and 3 candles with Peltier elements connected in series to the power and efficiency produced with a time duration of 120 seconds. Based on thos research, it shown that this thermoelectric generator is capable to producing 0.01200 Watt with a temperature difference of 10 oC for 1 candle, and producing 0.02920 Watt with a 12 oC temperature for 2 candles and generating 0.04107 Watt with a temperature difference of 14 oC for 3 candles. While the resulting efficiency is 0.033%, 0.057% and 0.092% each using 1, 2 and 3 candles for 120 seconds.